Methods for assessing management systems effectiveness - K. F. Abdullah (Вестник университета)
Management systems effectiveness analysis today is of great importance, as the conditions of the external environment are changing rapidly, which means that effective management systems must meet the challenges of the time. At the same time, it represents a certain complexity, since it involves the quan titative and qualitative indicators analysis. For this reason, there are practical ly no comprehensive assessment methods developed in the scientific world. Each method has its advantages and disadvantages, so researchers recommend the simultaneous use of several methods to assess the effectiveness of man agement system functioning from different aspects of its activities. Howev er, it is also quite problematic and requires several experts involvement who will make the assessment. A comprehensive analysis of scientific sources re vealing the essence of management systems, the management system effec tiveness concepts, as well as the main methods of evaluation has been car ried out. The author’s attempt to clarify the methodological apparatus based on the findings has been made. As the analysis result, the methodological ap paratus necessary to ensure the process of assessing management systems ef fectiveness has been clarified. The obtained conclusions made it possible to de velop the author’s method of assessing management systems effectiveness, which allows to assess both quantitative and qualitative performance indicators.